VILLAGE FINANCIAL MANAGEMENT ACCOUNTABILITY OF UNTER IWES DISTRICT IN SUMBAWA REGENCY - Wahyudi, Agus (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2019)
Act No. 6/2014 of the village have a large impact, where villagers have greater authority in financial management. It is also followed by the release of regulation of the minister of home affairs No. 113/2014 on the financial management of the village and regulation of regent of Sumbawa Regency No. 12/2015 on guidelines for the financial management of the village which is expected to help the government in the village work. This study is also in the underlying by the statement of one of the heads of villages in the subdistrict of Unter Iwes that still required an understanding of the financial management of the village especially the administration. Therefore, this study aimed to analyze the accountability of financial management of villages in villages in the subdistrict of Unter Iwes Sumbawa Regency. Village financial management referred to in this research is the village financial management stages include: planning, implementation, administration, reporting, and accountability. This type of research used in this research is descriptive quantitative research. The sample in this study is the village officials who have the duty and authority in the village financial management amounted to 56 samples. The data in this study were collected through a questionnaire and the results are validated by the results of interviews and documentation. Based on the quantitative analysis conducted on all aspects of planning, implementation, administration, reporting, and accountability for the conclusion that the financial management of villages in villages in the subdistrict of Unter Iwes Sumbawa already well underway. Where the results of the questionnaire have shown very good condition, as well as with the results of interviews have shown very good condition and results documentation have shown most of the village was able to provide the documents needed by researchers and it complies with the rules, but there are also villagers who were unable to show the documents required by the researcher. The results of this study contribute to the village in order to manage the finances of the village with more accountable in their work and orderly conduct admininistrative work.